HIGHER SCHOOL TRADITIONS: BORN TODAY AND IN DECADES LONG - Aleksey V. Pavlov; Natal’ya T. Eregina (Высшее образование в России)
The article examines the traditions of education and upbringing of students at the Yaroslavl Medical Academy. Among the best university traditions there are those which have a long history and also newborn. It is shown how adherence to tradition becomes a real instrument for formation the spiritual culture of students, attaching them to the standards of the medical community, the best examples of Russian culture, historical memory.